Distribution, metabolism and excretion of [1-14C]dolichol injected intravenously into rats. - Rip, J W (1985)
[1-14C]Dolichol mixed in vitro with rat serum and injected intravenously into rats was rapidly cleared from the circulation in a manner consistent with a two-compartment model. About 80% of the radioactivity recovered from animals killed after 1 day was in the liver, with smaller amounts being found in lung, carcass (internal organs removed), gastrointestinal tract and contents, and spleen. The kidneys, testes and heart contained little radioactivity, and the brain did not appear to take up any [1-14C]dolichol. The half-life for the turnover of radioactivity from [1-14C]dolichol in tissues varied considerably, being 2 days for the lung, 17 for liver and about 50 days for the carcass. After 1 day, and also after 4 and 21 days, most of the radioactivity in all tissues was as [1-14C]dolichol and as [1-14C]dolichyl fatty acyl ester, although a small amount of incorporation of [1-14C]dolichol radioactivity into phospholipids was also observed. Faeces collected over the first 4 days after injection contained 13% of the [1-14C]dolichol dose, but urine and expired air contained only small amounts of radioactivity. Radioactivity in faeces was nearly all as unchanged [1-14C]dolichol and as [1-14C]dolichyl fatty acyl ester. The [1-14C]dolichol remaining in liver after 21 days appeared to be in a pool (possibly lysosomes) where most of it was not subject to excretion.